(untitled) (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2017)
Arterial tree models have been successfully used to obtain a better understanding of all aspects hemodynamics of clinically relevant regions of the human body in order to diagnosis and applications in surgical planning. Basically, the models can be classified into: anatomical, lumped parameter, fractal and optimized. This work focuses on the generation of 3D optimized models based on Constructive Constrained Optimization (CCO) method equipped with a model to account for the Fahraeus Lindqvist effect, which indicates that the blood viscosity depends on the diameter of the vessel and discharge hematocrit through a nonlinear function. In this work, data morphometrics from models are compared with those of real coronary trees and the effective admittance of the models is investigated.